2022
DOI: 10.1007/s10639-022-11074-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance expectancy of E-learning on higher institutions of education under uncertain conditions: Indonesia context

Abstract: Performance expectancy is the expected impact of a technology’s functional advantage even in uncertain conditions. This study suggests that the learning collaboration quality, information quality, and course content support impact the actual use of e-learning and satisfaction perceived by the user, resulting in performance expectancy that meets stakeholder expectations. This study outlines the theoretical model for defining student success in e-learning systems through a theory of online collaborative learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…It shows that most users have felt satisfied with the information provided by BSI through mobile banking, hence significantly making Indonesians intent on adopting BSI mobile banking. These validate the existing results from Cidral et al (2018), Sewandono et al (2022), Shahzad et al (2021), andTarhini et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…It shows that most users have felt satisfied with the information provided by BSI through mobile banking, hence significantly making Indonesians intent on adopting BSI mobile banking. These validate the existing results from Cidral et al (2018), Sewandono et al (2022), Shahzad et al (2021), andTarhini et al (2019).…”
Section: Discussionsupporting
confidence: 90%
“…Originally, Venkatesh et al (2012) defined PE as the extent to which individuals believe that their job performance is improved using technology. However, depending on the nature of their research, several researchers (such as Sewandono et al, 2022;Batucan et al, 2022) have explored PE from a different viewpoint concerning habitual behaviour. For this study, we define PE as the degree to which the use of digital census tools (such as CAPI) has enabled enumerators to effectively carry out their duties.…”
Section: Performance Expectancymentioning
confidence: 99%
“…As a relatively new area of study, there may not be any prior research that specifically examines the relationship between PE and digital census. However, PE has been used in other studies to establish its relationship with various technology outcomes, such as faculty research, where Sewandono et al (2022) found that information quality, collaboration quality, and satisfaction with system use all have a positive and significant relationship with PE. Using the extended UTAUT model to explain factors affecting online technologies, Batucan et al (2022) concluded that there was an insignificant relationship between PE and BI, but they explained that the level of interactivity the system affords and the actual enjoyment from the system can significantly influence PE.…”
Section: Performance Expectancymentioning
confidence: 99%
“…The applications also allow many learners to create and use a private space on the Internet, through a website, which is used to publish information and electronic lessons [9]. The use of virtual classrooms in the educational process is considered one of the most important means aimed at delivering science and knowledge to humans through the Internet and its applications, as well as virtual classrooms contribute to supplying a wide range of valuable educational tools and advanced tools [10]. Also, Google educational applications provide the educational process with benefits such as allowing communication between the teacher and the student more efficiently than traditional methods, as well as providing the teacher with educational means to deliver information to the student, keeping in mind that these applications are free [11].…”
Section: Introductionmentioning
confidence: 99%